Educational Psychology - Anita Woolfolk (New York Pearson, 2021)
Anita Woolfolk Hoy was born in Fort Worth, Texas, where her mother taught child development at TCU and her father was an early worker in the computer industry. She is a Texas Longhorn; all of her degrees are from the University of Texas, Austin, the last one a PhD After graduating, she was a psychologist working with children in elementary and secondary schools in 15 counties of central Texas. She began her career in higher education as a professor of educational psychology at Rutgers University, and then moved to The Ohio State University in 1994. Today she is Professor Emerita at Ohio State. Anita's research focuses on motivation and cognition, specifically, students' and teachers' sense of efficacy and teachers' beliefs about education. For many years she was the editor of Theory Into Practice, a journal that brings the best ideas from research to practicing educators. With students and colleagues, she has published more than 150 books, book chapters and research articles.Anita has served as Vice-President for Division K (Teaching & Teacher Education) of the American Educational Research Association and President of Division 15 (Educational Psychology) of the American Psychological Association. Before completing this 14th edition of Educational Psychology, she collaborated with Nancy Perry, University of British Columbia, to write the 2nd edition of Child Development (Pearson, 2015), a book for all those who work with and love children.
Keywords: Educational Psychology